THE ROLE OF INTERNATIONAL ACTORS IN ENHANCING LABOUR RELATIONS IN AFRICA: A CASE STUDY OF THE KENYAN SKILLED LABOUR FORCE - Kaituko, MPA, Geoffrey (IJRDO - Journal of Social Science and Humanities Research, 2023)
Africa as a continent has been identified as the most rapidly growing and developing regional labour market in the world. The region has also experienced a high population growth rate in the last four decades making it the youngest continent in the world. As a result, it has experienced high average economic growth rate which can be attributed to its young and skilled labour force. Industrialization and globalization have resulted in an increased demand for skilled labour force and the rapidly growing skilled labour force on the continent has resulted in many countries in Africa being forecasted to be key economic hubs in the future. Labour. This study has been guided by the Marxist theory in analyzing the role of on challenges faced by the organization in Kenya’s informal employment sector. The study has conducted a quantitative survey on 112 participants derived from Ministry of Labour and Social Protection of the Republic of Kenya, and the Central Organization of Trade Unions of Kenya (COTU-K). Data collected from trade unions offices in Kenya, and the Ministry of Labour and Social Protection was in the form of primary and secondary data. Using the SPSS software to analyze data statistically, this study identified the key strategies applied by the International Actors on the challenges faced by the organization in an attempt to ensure decent working conditions for the Kenyan employees.According to the findings of this study, International Actors play a key role in ensuring decent work and inclusivity in the informal sector through the promotion of skilled labour force rights and also advocating for better wages and salaries in the sector. The organization has also been found to play a key role in the promotion of diversity and inclusion of employees in the informal sector through public education programmes and campaigns. This has created more employment opportunities for women and disabled employees and other groups in the country. The success of the execution of these roles has been largely dependent on the skilled labour force helpdesk established by the International Actors such as the International Labour Organization (ILO), International Organization for Migration (IOM), the World Bank and the US Department of Labour.This study has also established the role of the International Actors in the development of labour laws in Kenya. Among the major strategies applied by the organization are advocating for the development of laws governing skilled labour, minimum wages, elimination of child and forced labour and the independence of trade unions. Other strategies include the development of collaborations with the Ministry of labour and COTU-K to aid in the development of labour laws to protect local skilled labour force from capitalist employers. However, these organizations have not been able to execute its mandate effectively in the country due to several reasons identified by this study. Declining influence of the organizations in local affairs, low ratification of international conventions, lack of representation of the Ministry of Labour and Social Protection and COTU, and also the bureaucratic structure of the organization that hinder quick decision making.The study concludes that the challenges faced in Kenya are due to the communication and collaboration gap that exists between these organizations and the Kenyan labour authorities. Factors such as the organizational structure of the International Actors enhancing skilled labour force have contributed to the challenges, major challenges are linked to poor collaboration. It, therefore, recommends the need to fully ratify conventions C189 and C190 of ILO, need for full cooperation within Interstate and state to state and Inter-agency for achieving key National Labour Standards, and need to support good governance; transparency and democratic leadership to enhance growth of trade unions and enshrine it in Kenya’s Skilled Labour force.